Peran Kepala Madrasah dalam Pengembangan integrasi Kultur dan karakter Akhlak Mulia berbasis Pesantren di Madrasah Tsanawiyah Miftahul Qulub Tawar Gondang Mojokerto - Misluhah, Misluhah (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2017)
The low quality of Indonesian education was also shown Data Research and Development (2003) in Panjaitan (2014) that of 146 052 elementary schools in Indonesia was only 8 schools who gained worldwide recognition in the category of The Primary Years Program (PYP). Of the 20,918 junior high schools in Indonesia, there are only 8 schools that received world recognition in the category of The Middle Years Program (MYP), and from 8,036 SMA, only 7 schools received world recognition under The Diploma Program (DP). The purpose of this research is to describe the role of Principals in the Integration Development of Culture and Moral character-based Noble Boarding School in Fresh Qulub MTs Miftahul Gondang Mojokerto, Based on the discussion can be summarized as follows: 1) The model of character education in adolescents aims to develop personality traits. Character education is done by acting speech directive (advice, orders, suggestions, etc.). Character education models in adolescents are integrated into various learning activities, school rules, and extracurricular activities or media posters attached to school walls. 2) The implementation of character education in MTs Miftahul Qulub Fresh Gondang Mojokerto maximum run boarding school because the curriculum is integrated with the school curriculum, in which the achievement of values ​​in schools is a prerequisite for the achievement of values ​​in schools. In addition, students in MTs Miftahul Qulub Fresh Gondang Mojokerto are students in boarding Miftahul Qulub Fresh Gondang Mojokerto, so the location is in one place, then facilitate monitoring and evaluation. 3) Implementation of character education in Madrasah Tsanawiyah Miftahul Qulub Tawar Gondang Mojokerto can be grouped into three domains namely: (l) affective. character education planting resulted in a change of attitude, through habituation on an ongoing basis both in schools and at schools to make students have certain characters such as steadfastness, good morals, self, and others; (2) cognitive linking character education into subjects give students an understanding of the values ​​of character and the importance of character in everyday life, so as to stimulate awareness of the students to practice the values ​​of characters in everyday life; And (3) psychomotor: through the learning experiences that students receive both in the pesantren and at school, they have the most embodied abilities into behavioral forms in everyday life. This practice is a continuation of the affective and cognitive spheres in the form of behavioral trends. Behavior is influenced by his learning experience through habituation that form the character inherent in him